PENINGKATAN HASIL BELAJAR DENGAN MENGGUNAKAN MODEL PEMBELAJARAN SNOWBALL THROWING PADA MATA PELAJARAN IPS DI KELAS V SD - Ginting, Masta (Jurnal Dinamika Pendidikan, 2016)
ABSTRACTThis study aims to determine the material improvement of learning outcomes of socialscience subject with the topic Dutch colonization in Indonesia. This study is a classroomaction research (CAR). The subjects were fifth grade students totaling 28 students. Thetechnique of data analysis in this study is a qualitative description. On the pretest,students who completed 5 people with a percentage of 17.86%, which did notcomplete as many as 23 people with a percentage of 82.14% and the average score of48.11. In cycle I students who pass as many as 10 people with a percentage of 35.71%,which did not complete as many as 18 people with a percentage of 64.29% and theaverage value of 50.49. In the second cycle complete as many as 24 people with apercentage of 85.71% and students who did not complete as many as four people witha percentage of 14.29% and the average score 81.20 level in the classical completenesssecond cycle is 85.71%.Keywords: Snowball Throwing, Learning Outcomes, Social ScienceABSTRAKPenelitian ini bertujuan untuk mengetahui peningkatan hasil belajar IPS materipenjajahan belanda di indonesia. Jenis penelitian ini adalah penelitian tindakan kelas(PTK). Subjek penelitian adalah siswa kelas V yang berjumlah 28 siswa. Adapun teknikanalisis data dalam penelitian ini adalah deskripsi kualitatif. Pada pretest, siswa yangtuntas sebanyak 5 orang dengan persentase 17,86 %, yang tidak tuntas sebanyak 23orang dengan persentase 82,14 % dan nilai rata-ratanya sebesar 48,11. Pada sikulusI siswa yang tuntas sebanyak 10 orang dengan persentase 35,71 %, yang tidak tuntassebanyak 18 orang dengan persentase 64,29 % dan nilai rata-ratanya 50,49. Padasiklus II tuntas sebanyak 24 orang dengan persentase 85,71 % dan siswa yang tidaktuntas sebanyak 4 orang dengan persentase 14,29 % dan nilai rata-ratanya 81,20tingkat ketuntasan secara klasikal siklus II adalah 85,71 % .Kata Kunci : Snowball Throwing, Hasil Belajar, IPS